Menginisiasi desain kain Jumput- Batik khas Banyunibo - Mahirta, Mahirta; Savitri, Mimi; D.S. Nugrahani; Arumdati, Fayeza Saliz (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2023)
Community around Banyunibo temple has been trained to produce hand-painted batik for the last 5 years. This training have improved their skill, enabling them to produce real hand-painted batik. However, their products have not sold well, moreover during the pandemic era caused by Covid-19. After carried out interview and discussion in survey phase, it is known that the community has problem in marketing their hand-painted batik and wish to have unique Banyunibo batik product. Based on the condition, the community service team of Archaeology Department, Faculty of Cultural Sciences conduct a community empowerment program with an intention to help Banyunibo community in creating Banyunibo’s batik motifs inspired by the reliefs of Banyunibo temple, unique, and potentially sale well. This community service conducted using skill building and empowerment approach, with the purpose to create active and direct invlolvement of the community during the activity. Hand-stamp batik introduced as an alternative to produce a less-expensive batik than hand-painted batik, therefore can compete well in batik market. Relief-inspired motifs created through distortion and stylization from the original temple reliefs. These motifs, made by stamp application technique, is also combined with jumput technique, creating a unique jumput - batik product that hopefully can increase the buying power of Banyunibo’s batik. ==== Komunitas pembuat batik di sekitar Candi Banyunibo telah dilatih membuat batik tulis sejak lima tahun terakhir. Hasil kegiatan tersebut telah meningkatkan keterampilan mereka dalam membuat produk batik tulis. Namun, daya jual batik produk mereka masih rendah di pasaran, terlebih lagi pada masa pandemi Covid-19. Setelah melakukan wawancara dan diskusi pada tahap survei, diketahui bahwa masyarakat memiliki kendala berupa kesulitan memasarkan batik tulis dan keinginan untuk memiliki batik khas Banyunibo. Berdasarkan keadaan tersebut, tim pengabdian kepada masyarakat Departemen Arkeologi UGM melakukan program pemberdayaan komunitas dengan pembinaan batik cap dan pembuatan motif batik khas Banyunibo yang terinspirasi dari relief pada Candi Banyunibo. Pengabdian masyarakat ini dilakukan menggunakan pendekatan berupa pendampingan dan pemberdayaan masyarakat dengan tujuan agar masyarakat dapat terlibat langsung dan aktif dalam pelaksanaan pendampingan ini. Batik cap sebagai alternatif diperkenalkan untuk menghasilkan batik yang tidak semahal batik tulis sehingga harganya dapat bersaing di pasaran. Motif inspirasi relief candi diciptakan melalui proses distorsi dan stilasi dari gambar asli relief candi. Motif batik yang dihasilkan dengan teknik cap tersebut juga dikombinasikan dengan teknik jumput sehingga menghasilkan motif khas Banyunibo yang diharapkan dapat meningkatkan daya jual dari batik Desa Banyunibo.